Defection from the Faith Prior to 1983 Code of Canon Law: Canon 1117 - Donlon, James (Roman replies and CLSA advisory opinions 1999, 1999)
The Tribunal has received a marriage nullity case in which one of the parties to the marriage had been baptized Catholic but had by a formal act abandoned the faith and joined another faith. This defection took place prior to the promulgation of the 1983 Code of Canon law and is well-documented. The marriage, to another non-Catholic, took place after 1983, before a non-Catholic celebrant. No dispensation from the obligation to observe canonical form had been sought or granted. The person saw no reason to seek one. Was this former Catholic bound to the observance of the canonical form or not, since the defection took place prior to the promulgation of the 1983 Code?